HOW YOUNG MINDS ARE ADVANCING SCIENCE? - Ismatov Shamshod Farkhod ugli (TADQIQOTLAR, 2025)
Abstract Young scientists play an important role in the development of modern science. Their desire for new knowledge, creativity and willingness to experiment allow them to find non-standard solutions and develop innovative technologies. This article examines the key areas in which young people have a significant impact on scientific progress, as well as the factors contributing to their success. Particular attention is paid to the challenges faced by young researchers and possible ways to overcome them.